Pembuatan Komposit Matrik Resin Fenolik Di Perkuat Paduan Logam Dan Bagasse Ash Menggunakan Metode Metalurgi Serbuk - Muhammad Fadhil; Sukanto Sukanto; Erwanto Erwanto; Abdul Budi; Agus Wanto (Politeknik Manufaktur Negeri Bangka Belitung, 2026)
This study aims to develop phenolic resin-based composite materials with the addition of aluminum, brass, silica, and bagasse ash powders as reinforcing materials, using powder metallurgy methods. The specimen manufacturing process was carried out through mixing stages using a ball mill, hot compaction with pressure variations of 5000 psi, 53 00 psi, and 5600 psi, and sintering at a temperature of 130°C for 10 minutes. The tests were conducted at the Mechanical Engineering Laboratory of the Bangka Belitung State Polytechnic, including hardness tests (ASTM E110-14) and density tests (ASTM B962-17). The results showed that the pressing pressure and composition variations had a significant effect on the mechanical properties of the composite. The highest hardness value was obtained at a composition of 35% with a pressure of 5600 psi, while the optimal density was obtained at a composition of 31% with a pressure of 5300 psi. Overall, the combination of the right process parameters proved to be able to improve the quality of the composite, so that this material has the potential to be used as an alternative to asbestos-based brake pads.